2016
DOI: 10.1016/j.mayocp.2015.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Rehabilitation Program Adherence and Functional Capacity Among Women: A Randomized Controlled Trial

Abstract: clinicaltrials.gov Identifier: NCT01019135.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
107
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(110 citation statements)
references
References 40 publications
0
107
3
Order By: Relevance
“…The overall adherence was 64%. The results did not clearly favor any model (73). This study suggested that offering women alternative models for cardiac rehabilitation services did not promote adherence.…”
Section: Patient/health Care Provider Team-based Engagement Strategiesmentioning
confidence: 68%
“…The overall adherence was 64%. The results did not clearly favor any model (73). This study suggested that offering women alternative models for cardiac rehabilitation services did not promote adherence.…”
Section: Patient/health Care Provider Team-based Engagement Strategiesmentioning
confidence: 68%
“…Further, the patient's experience with an exercise program is vital for predicting attendance (33). It is important to note, providing RPE ranges alone may not achieve the target HR ranges needed for HIIT.…”
Section: Discussionmentioning
confidence: 99%
“…This could be due to cultural and religious factors [10]. Whether there is tailoring of women's classes to their unique needs remains a question for investigation, as is what adherence rates are achieved [32]. Programs would be prudent to focus in particular on interventions to address obesity and mental illness as these are very common CV risk factors for women in the region [33].…”
Section: Accepted Manuscript 14mentioning
confidence: 99%